Comparisons between glucose analogue 2-deoxy-2-((18)F)fluoro-D-glucose and (18)F-sodium fluoride positron emission tomography/computed tomography in breast cancer patients with bone lesions - Capitanio, Selene (World J Radiol, 2016)
AIM: To compare 2-deoxy-2-((18)F)fluoro-D-glucose((18)F-FDG) and (18)F-sodium ((18)F-NaF) positron emission tomography/computed tomography (PET/CT) accuracy in breast cancer patients with clinically/radiologically suspected or known bone metastases. METHODS: A total of 45 consecutive patients with breast cancer and the presence or clinical/biochemical or radiological suspicion of bone metastatic disease underwent (18)F-FDG and (18)F-fluoride PET/CT. Imaging results were compared with histopathology when available, or clinical and radiological follow-up of at least 1 year. For each technique we calculated: Sensitivity (Se), specificity (Sp), overall accuracy, positive and negative predictive values, error rate, and Youden’s index. McNemar’s χ(2) test was used to test the difference in sensitivity and specificity between the two diagnostic methods. All analyses were computed on a patient basis, and then on a lesion basis, with consideration ofthe density of independent lesions on the co-registered CT (sclerotic, lytic, mixed, no-lesions) and the divergent site of disease (skull, spine, ribs, extremities, pelvis). The impact of adding (18)F-NaF PET/CT to the work-up of patients was also measured in terms of change in their management due to (18)F-NaF PET/CT findings. RESULTS: The two imaging methods of (18)F-FDG and (18)F-fluoride PET/CT were significantly different at the patient-based analysis: Accuracy was 86.7% and 84.4%, respectively (McNemar’s χ(2) = 6.23, df = 1, P = 0.01). Overall, 244 bone lesions were detected in our analysis. The overall accuracy of the two methods was significantly different at lesion-based analysis (McNemar’s χ(2) = 93.4, df = 1, P < 0.0001). In the lesion density-based and site-based analysis, (18)F-FDG PET/CT provided more accurate results in the detection of CT-negative metastasis (P < 0.002) and vertebral localizations (P < 0.002); (18)F-NaF PET/CT was more accurate in detecting sclerotic (P < 0.005) and rib lesions (P < 0.04). (18)F-NaF PET/CT led to a change of management in 3 of the 45 patients (6.6%) by revealing findings that were not detected at (18)F-FDG PET/CT. CONCLUSION: (18)F-FDG PET/CT is a reliable imaging tool in the detection of bone metastasis in most cases, with a diagnostic accuracy that is slightly, but significantly, superior to that of (18)F-NaF PET/CT in the general population of breast cancer patients. However, the extremely high sensitivity of (18)F-fluoride PET/CT can exploit its diagnostic potential in specific clinical settings (i.e., small CT-evident sclerotic lesions, high clinical suspicious of relapse, and negative (18)F-FDG PET and conventional imaging).